MACHINE LEARNING BASED CONTAMINATION DETECTION IN WATER DISTRIBUTION SYSTEM - Zede (Zede Journal of Ethiopian Engineers and Architects, 2024)
Water is a necessary component of all human activities. According to the United Nations World Water Assessment Program, every day, 2 million tons of sewage, manufacturing, and agricultural waste are discharged into the world’s water. Due to population demands and dwindling clean water supplies as well as available water pollution management mechanisms; there is an urgent need to use computational methods to intelligently manage available water. This paper proposes artificial neural networks, specifically, Convolutional Neural Networks, for automated water impurity detection. To refine the model, the picture of turbid water in the pipe was used to detect events. The algorithm of deep learning achieved 96.3 percent accuracy after extensive training with a dataset of 4220 images reflecting various levels of contamination. This shows that, the model can be used in water system pollution detection.